"Lifestyle profile of condominium dwellers and marketing implication" / Wan Nasyatul Husna Wan Ishak - Wan Ishak, Wan Nasyatul Husna (2000)
This study attempts to delineate the condominium dwellers' lifestyle dimensions, their desired condominium physical characteristics and attributes and socio-demographics in the more prestigious and less prestigious areas. The study also attempts to evaluate the relative importance of these dimensions in differentiating between the two groups of condominium dwellers. Six lifestyle dimensions, eleven socio-demographics and five condominium physical characteristics and attributes variable were examined and compared to differentiate between the two groups of condominium dweller. Only two lifestyle dimensions, six socio-demographics and two physical characteristics and attributes variables were found to be significant in differentiating between the two groups of condominium dwellers. The results of the lifestyle dimensions reveal that condominium dwellers in more prestigious area are more "artistically-biased", like art galleries and enjoy attending concerts. Alternatively, their counterparts in the less prestigious area are more "neighborhood-conscious" , emphasize a neighborhood at the same social class and prefer to have neighbors of the same race. A stepwise discriminate analysis was used to differentiate between the two groups of condominium dwellers in term of lifestyle dimensions, condominium physical characteristics and attribute variables and sociodemographics. The findings of the study could have significant implications for condominium development in Malaysia, particularly with respect to formulating marketing strategies, government policies and social communication programs